THE EFFECT OF BUDGETS’ PROPORTION AND NON-FINANCIAL FACTORS ON THE AUDIT RESULTS OF LOCAL GOVERNMENTS’ FINANCIAL STATEMENTS IN INDONESIA - Nurdiono Nurdiono; Slamet Sugiri; Abdul Halim; Gudono Gudono (Journal of Indonesian Economy and Business (JIEB), 2016)
Local governments’ financial statements that obtain unqualified opinion until the end of 2011 were still relatively few in number. This study aims to empirically examine the effect on the audit results of the financial statements of local governments in Indonesia of the budgets’ proportion, the effectiveness of the internal audit, the follow-up to the Supreme Audit Board’s findings, the Supreme Audit Board’s opinions from earlier periods, and the competence of the available human resources to understand the audit results of the Supreme Audit Board. Budget management has become very important since it lays out a detailed plan for the expenditure and revenue of the local governments, so that it can be accountable to the public. This study used a sample of 434 Indonesian Local Governments’ financial statements of 2011 and a logistic regression analysis. This study used primary and secondary data to uncover the phenomena that the local governments’ financial statements which received an unqualified opinion from the Supreme Audit Board were still relatively few in number. The results of this study showed that the budgets’ proportions of local governments are negatively significant in affecting the audit results of the financial statements of the local governments. The Supreme Audit Board’s opinions from earlier periods positively influenced the audit results of the financial statements of local governments. Whereas the variables of the effectiveness of internal controls, the follow-up to the Supreme Audit Boards’ findings, and the competence of the human resources do not significantly influence the audit results of the financial statements of local governments. The results of this study can contribute both theoretically and practically to the quality of the local governments’ financial statements. Keywords: budgets’ proportion, human resources, competency, opinions, audit quality.